2017
DOI: 10.1136/bmjopen-2017-017084
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of severe acute malnutrition among children under 5 years of age in Nepal: a community-based case–control study

Abstract: BackgroundMalnutrition is one of the leading causes of morbidity and mortality among children under the age of 5 years in low and middle income countries like Nepal. Children with severe acute malnutrition (SAM) are nine times more likely to die than children without malnutrition. The prevalence of SAM has increased in Nepal over the past 15 years; however, the determinants of SAM have not been clearly assessed in the country.ObjectiveTo assess the determinants of SAM among children aged 6–59 months in the Bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
114
8
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(155 citation statements)
references
References 24 publications
27
114
8
6
Order By: Relevance
“…The possible explanation for this would be the exclusive breastfeeding rather than early breastfeeding provides protective nutrition to the children for an extended period of time. This nding is in agreement with ndings from Nepal and India [45,46,48].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The possible explanation for this would be the exclusive breastfeeding rather than early breastfeeding provides protective nutrition to the children for an extended period of time. This nding is in agreement with ndings from Nepal and India [45,46,48].…”
Section: Discussionsupporting
confidence: 93%
“…Exclusive breastfeeding practice in this study was signi cantly associated with SAM. This nding was comparable with the studies from Nepal and Pakistan [11,45,46]. The nding highlights the importance of exclusive breastfeeding from which children receive nutrition that have several bene ts including reduction in gastrointestinal infection [47].…”
Section: Discussionsupporting
confidence: 87%
“…Several studies from Bangladesh, Pakistan and our country observed a correlation between low parental education and increased risk of wasting in children. [10][11][12][13][14][15] Islam and others in their study concluded that poverty is a very important risk factor for wasting as are unsafe drinking water sources and lack of latrines. Similar observations were made by Meshramand others.…”
Section: Number Of Patients %mentioning
confidence: 99%
“…Baily W observed that the infants of adolescent mothers were admitted to hospitals with malnutrition at an earlier age than infants of older mothers. 19,15 Sanitation facility in present study was assessed through the presence of toilet facility, source of drinking water and availability of proper drainage facility. Toilet facility was present in 40% of the family whereas 60% of the family defecated in open.…”
Section: Number Of Patients %mentioning
confidence: 99%
“…Previous studies conducted in the region have found that poor socioeconomic status, lower level of parental education, younger age of mother at birth, short birth interval, and initiation of complimentary feeding are important determinants of undernutrition among under-five children. 2527 We also observed significant nutrition disparity by household socioeconomic status. In populous countries like Bangladesh, India, and Pakistan, almost half of the children in poorest households were underweight.…”
Section: Discussionmentioning
confidence: 69%